In Memory Energy Application for Resistive Random Access Memory. (19th August 2021) - Trotti, Paola; Oukassi, Sami; Molas, Gabriel; Bernard, Mathieu; Aussenac, François; Pillonnet, Gaël
Abstract: This work explores the innovative concept of a hybrid dual‐behavior device, based on emerging nonvolatile memory technology, for both data retention and energy storage. RRAM (resistive random access memory) is considered a major candidate as next‐generation memory, thanks to its promising performances in terms of scalability and CMOS process compatibility. Its working mechanisms, based on faradaic processes, motivate the study on the feasibility of operating RRAM also as energy storage element. To evaluate the energy capability, various electrochemical characterizations on state‐of‐the‐art RRAM are presented. The highly resistive electrolyte, extremely small physical scale (nm), and current range (pA), put in quite a critical framework, far from conventional solid‐state batteries. Cyclic voltammetry tests reveal that although no oxidation peak appears during the redox cycle, the cells behave as standard electrochemical storage elements when investigating the impact of the scan rate, maximum positive voltage, and area on the reduction peak. Concentration and diffusion coefficients are derived, in the order of 10 −12 cm 2 s −1 and few mmol cm −3, respectively, while energy storage capability amounts to 3.5 pJ µm −2 . Finally, design concepts are proposed, where RRAM "in‐memory energy" technology would be a newfangled approach to meet the needs of various emerging and standard applications. Abstract : A novel concept for both energy and information storage is presented, where the two operative modes are integrated into the same device. Based on resistive random access memory technology, the energy storage behavior is evaluated through cyclic voltammetry tests, and energy and power densities are derived. The results show potential for future study to bring the concept to the application level.